Occurrence of isopod parasites in clupeids off Chennai coast, India - Sethi, Satyanarayan (Indian Journal of Fisheries, 2012)
The study was carried out to investigate the incidence of isopod parasites in clupeids, with special emphasis on the Indianpellona fish, Pellona ditchela . Two species of isopods, Joryma hilsae and Joryma sawayah were found infecting this fish.The isopods of the genus Joryma are typical Indo-Pacific genus, found infecting the gills of marine fishes. However, this isthe first report of these two species in Indian pellona, P. ditchela along the Bay of Bengal off Chennai coast, India. Theprevalence (%) of J. hilsae and J. sawayah in P. ditchela recorded during the present investigation were 17.7 and 32.3respectively. Cymothoids are common isopod parasites of marine fishes and their infection can cause serious damages to thefishes.